2010 2nd IEEE International Conference on Information Management and Engineering 2010
DOI: 10.1109/icime.2010.5478171
|View full text |Cite|
|
Sign up to set email alerts
|

Notice of Retraction: Unraveling the different effects of quality and human resource management aspectson organizational performance

Abstract: This study examined the relationship between quality and human resource management (HRM) aspects on organizational performance (OP). The study also determined the effects of quality and management aspects on OP. Consequently it assessed the different effects of quality and human resource management aspects on OP. Data of the study was collected from a sample of 200 management staff of Malaysian manufacturing companies. The study found that all of the quality and HRM aspects were related to OP. The study also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…This is in line with the findings of this study which indicated that attitudinal aspect has emerged as the second most important factor in enhancing business performance. This is among the required human capital aspects in Malaysian logistics companies [2]- [4] and [9] Findings of this study are in tandem of previous studies [9], [28], [44] and [45]. The results of the study also are able to validate the applicability of RBV theory which explains the importance of resources (human capital) to create competitive advantage and increase business performance in logistics companies.…”
Section: Discussionsupporting
confidence: 78%
“…This is in line with the findings of this study which indicated that attitudinal aspect has emerged as the second most important factor in enhancing business performance. This is among the required human capital aspects in Malaysian logistics companies [2]- [4] and [9] Findings of this study are in tandem of previous studies [9], [28], [44] and [45]. The results of the study also are able to validate the applicability of RBV theory which explains the importance of resources (human capital) to create competitive advantage and increase business performance in logistics companies.…”
Section: Discussionsupporting
confidence: 78%